Old breed general : how Marine Corps General William H. Rupertus broke the back of the Japanese in World War II from Guadalcanal to Peleliu /: how Marine Corps General William H. Rupertus broke the back of the Japanese in World War II from Guadalcanal to Peleliu. (2022) - Peacock, Amy Rupertus, 1970-; Brown, Don, 1960-
No abstract available